Cytotoxicity of Physic Nut (Jatropha curcas L., Euphorbiaceae)Latex by Agar-Overlay - Siregar, Fazwishni (Jurnal Kedokteran YARSI, 2015)
Jatropha curcas L. latex has been used as traditional medicine to cure various infections among others are to cure toothache, apthae, as a mouth rinse to treat bleeding gums, as a hemostatic, and a wound dressing. To be used as herbal medicine, scientific investigation including toxicological studies must be conducted. The aim of these studies was to evaluate the cytotoxicity of J. curcas latex by agar overlay technique as part of toxicological study. Fibroblasts L929 were cultured in Petri dishes to confluence, and a layer of agar was then added. After staining the cells with neutral red, diluted latex (0.4-15% w/v) imbibed in filter paper were applied to the agarsurface and incubated for 24 hours. Evaluation was based on the zone of decoloration and lysis indices. Result showed that there was zone of decoloration from 2-5 mm in diameter that was all in the index 2 (less than 5 mm) from 5 index decoloration classification. Lyses cells were not observed in the decoloration zone, which could be interpreted as a coagulative necrosis. It may be concluded thatJ. curcaslatex has a moderate cytotoxic activity and necrotic coagulation in an agar-overlay technique usingfibroblast L929.